Investigation effect of depressant additives on physicochemical properties of engine oil - S. V. Pashukevich (Омский научный вестник)
In this work, laboratory tests of M8G2k engine oil are carried out with the introduction of SAP 110 depressants by Shell Additives and Lz 6662 by Lubrizol and their impact on the properties of the lubricant in question are assessed separately. During the tests, the values of the following indicators of engine oils are obtained: kinematic viscosity at 100 °C, base number, flash point in an open crucible, pour point and content of active elements (calcium, zinc). With the help of the SI-010 bench installation, the values of anti-pitting properties are indicated, as well as experiments are carried out on the NAMI-1m and Petter W-1 installations, with their help the tendency to the formation of low- and high-temperature deposits in the internal combustion engine (ICE) and the assessment of anti-corrosion properties respectively. To analyze the detergent properties of the engine oil under consideration, a test procedure are carried out on a D-240 tractor engine. Positive laboratory test results give grounds to recommend using M8G2k engine oil containing SAP 110 or Lz 6662 additives for the D-240 engine manufactured by MMZ.